(untitled) (Journal of Energy and Safety Technology (JEST), 2023)
In Malaysia, escalator accidents caused injuries or fatalities. As a result, a forensic engineering technique was employed to look into the real causes of an escalator malfunction. There was escalator that occurred in 2016, KL Sentral. The escalator accident in 2016. The escalator step displacement is the clearance of a step along the vertical and lateral axes. According to BS EN 115-2017, a step’s clearance shall be measured. Step alignment of the escalator steps pass through the comb will be affected by step displacement that is outside of the permitted range, either the lateral or vertical direction that led to collision. The alignment of the escalator steps that moving through the comb will be hampered by step displacement that is more than the standard and it may result in a collision between the two parts on either the upper landing platform or lower landing platform. The impact from the collision of steps and combs may also injured escalator passengers. Hence, the clearance of the step in the vertical and lateral direction at any time. It is crucial to inspect and measure the step displacement parameter for both lateral and vertical step displacement. Improper installation of the step axle slot component on the step shaft; lateral step displacement is caused by clearance between a bush and stopper ring component, while vertical step displacement is caused by clearance between an axle slot and bush component. Prior, installation of those steps must be done carefully to avoid any clearance to prevent step displacement’s accident occurred.